2019
DOI: 10.3389/fnut.2019.00186
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of Pistachio Intake on Postprandial Glycemic and Gut Hormone Responses in Women With Gestational Diabetes or Gestational Impaired Glucose Tolerance: A Randomized, Controlled, Crossover Study

Abstract: Long-term consumption of pistachios could potentially improves glucose homeostasis. Impaired postprandial glucose, insulin, and glucagon-like peptide-1 (GLP-1) responses have been reported in gestational diabetes mellitus (GDM) patients. The objective of this study was to evaluate the acute effects of two isocaloric test meals, 42 g pistachios and 100 g whole-wheat bread (WWB) on postprandial glucose, insulin, and gut derived incretin levels in Chinese women with gestational impaired glucose tolerance (GIGT) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…At the end of the study, statistically significant improvement was seen in levels of fasting blood sugar (FBG) however, no significant effect was seen on HbA1c and insulin levels. In a recent study conducted to evaluate the acute effects of two isocaloric test meals, 42 g pistachios and 100 g whole-wheat bread (WWB) on postprandial glucose, insulin, and gut derived incretin levels in Chinese women with gestational impaired glucose tolerance (GIGT) or gestational diabetes mellitus (GDM) suggested that pistachios are effective alternative to a low-fat, high-carbohydrate food to improve postprandial glucose, insulin, and GLP-1 response in women with GDM and GIGT [106]. The fiber, healthy fats, low available carbohydrate and carotenoid content of pistachios are the important nutrients involved in glucose metabolism as suggested by Bullo et al [107].…”
Section: Pistachio and Diabetesmentioning
confidence: 99%
“…At the end of the study, statistically significant improvement was seen in levels of fasting blood sugar (FBG) however, no significant effect was seen on HbA1c and insulin levels. In a recent study conducted to evaluate the acute effects of two isocaloric test meals, 42 g pistachios and 100 g whole-wheat bread (WWB) on postprandial glucose, insulin, and gut derived incretin levels in Chinese women with gestational impaired glucose tolerance (GIGT) or gestational diabetes mellitus (GDM) suggested that pistachios are effective alternative to a low-fat, high-carbohydrate food to improve postprandial glucose, insulin, and GLP-1 response in women with GDM and GIGT [106]. The fiber, healthy fats, low available carbohydrate and carotenoid content of pistachios are the important nutrients involved in glucose metabolism as suggested by Bullo et al [107].…”
Section: Pistachio and Diabetesmentioning
confidence: 99%
“…A randomized controlled study has reported the beneficial effects of a Mediterranean diet with additional extra virgin olive oil and pistachios on gestational diabetes mellitus, whose prevalence is increasing and becoming a major public health concern [ 117 ]. These data are supported by a later study showing that pistachios are an effective alternative to a low-fat, high-carbohydrate food in order to improve postprandial glucose, insulin, and GLP-1 response in women with gestational diabetes mellitus and with gestational impaired glucose tolerance [ 118 ].…”
Section: Nuts and Healthmentioning
confidence: 59%
“…Systematic reviews and meta-analyses of RCTs suggest beneficial effects on blood pressure, endothelial function and on markers of glucose and insulin metabolism (19,30) . For comprehensive reviews of the health effects of pistachio nuts, see Bullo et al (9) Plant-based diets Plant-based diets, which emphasise plant foods but do not necessarily fully exclude animal foods (31) , have become centre stage both for nutritional health and climactic/sustainability reasons. An evidence-based focus on one of nature's unprocessed, plant food snacks is therefore timely.…”
Section: Pistachios and Healthmentioning
confidence: 99%
“…Feng et al. Shanghai, China (9) Randomised Controlled Cross-over Trial. Two isoenergetic test meals: 42 g pistachios or 100 g whole wheat bread.…”
Section: San Carlos Gestational Diabetes Mellitus Prevention Study Madrid Spainmentioning
confidence: 99%
See 1 more Smart Citation